Dominant Pathogens Causing Leaf Spot Disease in Oil Palm Plants That Have Not Yet Produced (TBM) Using A Visual Approach and Control Strategy Recommendations - Riki Kurniawan Barus; Junaidi; Nurliana (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Leaf spot disease is a major constraint on immature oil palms because it can inhibit growth. This study aimed to identify leaf spot diseases, determine their incidence and prevalence, and establish the dominant disease affecting three-year-old immature oil palms. A descriptive field survey was conducted on 50 sample plants across Block A and Block B. Data were collected through visual observation of disease symptoms and analysed according to incidence, prevalence, severity, and dominance. The results identified two principal pathogens: Curvularia sp., with an incidence of 24%, and Fusarium sp., with 16%. Overall disease incidence reached 40%, while prevalence in both blocks was 100%. Curvularia sp. was the dominant disease, accounting for 60% of all cases. Although the severity of both diseases remained low, control measures are still required through plantation sanitation, routine monitoring, improved drainage, balanced fertilisation, removal of infected leaves, and appropriate fungicide application when necessary.